Exploring the Forest Structure and Floristic Composition Patterns of the Equatorial Chocó, Esmeraldas Province - Pablo Enrique Lozano Carpio; Bente Klitgaard; Walter Palacios; Janeth Santiana; Byron Medina; Carlos Morales; Juan Iglesias (Colombia Forestal)
The Chocó biome is characterized by high levels of precipitation, temperature, and endemism within a threatened landscape. This study compared the forest structure, floristic diversity, and forest ecology patterns of the Chocoan forests within the Esmeraldas province of Ecuador. In four permanent plots (4 ha), all trees with a diameter at breast height ≥ 10 cm were recorded. A data analysis regarding forest structure and floristic ecology showed a range of 441-624 individual trees per hectare with an average diameter of 21 cm, over a range of 10-202 cm, and a basal area of 24-34 m2. Meanwhile, the Simpson index exhibited great variation in alpha diversity, ranging from 9.12 to 45.12, with a total richness of 79 families and 360 species. In addition, a non-metric multidimensional scaling analysis revealed a high beta diversity. 18 endemic species were recorded, highlighting the importance of the bioregion for conservation.